2017
DOI: 10.1038/bjc.2017.288
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 safety, pharmacokinetic and pharmacodynamic study of the cyclin-dependent kinase inhibitor dinaciclib administered every three weeks in patients with advanced malignancies

Abstract: Background:Dinaciclib is a potent inhibitor of cell cycle and transcriptional cyclin-dependent kinases. This Phase 1 study evaluated the safety, tolerability and pharmacokinetics of various dosing schedules of dinaciclib in advanced solid tumour patients and assessed pharmacodynamic and preliminary anti-tumour activity.Methods:In part 1, patients were enrolled in escalating cohorts of 2-h infusions administered once every 3 weeks, utilising an accelerated titration design until a recommended phase 2 dose (RP2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 50 publications
2
33
0
Order By: Relevance
“…The 4T1 tumor-bearing mice were treated with either EZP6438 (34 mg kg −1 ; equivalent to 102.3 mg m −2 in human) or dinaciclib (8 mg kg −1 ; equivalent to 24 mg m −2 in human). The doses of EZH2i and CDK2i chosen were much lower than those of recommended phase 2 dose (RP2D: EPZ-6438, 800 mg m −2 ; dinaciclib, 50 mg m −2 ) 30,31 . For combination therapy, mice were administered tamoxifen after 3 days of CDKi or EZH2i monotherapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4T1 tumor-bearing mice were treated with either EZP6438 (34 mg kg −1 ; equivalent to 102.3 mg m −2 in human) or dinaciclib (8 mg kg −1 ; equivalent to 24 mg m −2 in human). The doses of EZH2i and CDK2i chosen were much lower than those of recommended phase 2 dose (RP2D: EPZ-6438, 800 mg m −2 ; dinaciclib, 50 mg m −2 ) 30,31 . For combination therapy, mice were administered tamoxifen after 3 days of CDKi or EZH2i monotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Dinaciclib has demonstrated antitumor activity in leukemia and other types of solid tumors as a single agent with a safety profile in patients 19,20 . Phase I clinical trial reports indicated that patients treated with dinaciclib at high dose (>29.6 mg m −2 , equivalent to >9.84 mg kg −1 in mice) experienced dose-dependent adverse effects 30,31 . To rule out the possible toxicity of dinaciclib (8 mg kg −1 ) combined with tamoxifen (4 mg kg −1 ) in mice for longer treatment schedule (21 day in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One of the concerns in the development of CDK inhibitors in the treatment of HCC is bone marrow suppression because many patients with HCC have preexisting cytopenia due to liver cirrhosis and splenomegaly. Although neutropenia was common in patients who received triweekly dosing of dinaciclib [28,36], a weekly schedule of dinaciclib was shown to be more tolerable [30]. In addition, our results revealed that CDKs 1 and 9, especially CDK9, might be the most crucial CDKs in HCC treatment.…”
Section: Discussionmentioning
confidence: 82%
“… 54 However, serious hematological toxicities may limit the use of dinaciclib as an antiviral drug. 58 …”
Section: Repurposed Approaches That Primarily Inhibit Viral Replicatimentioning
confidence: 99%